Needs Analysis For the Development Of Website-Based Interactive Infographic Modules in Arabic Grammar Learning - Abdul Hamid, Mohd Fauzi; Sahrir, Muhammad Sabri; Ab. Halim, Zulazhan; Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal; Sha'ari, Shaferul Hafes; Amiruddin, Ahmad Zaki (Ijaz Arabi Journal of Arabic Learning, 2024)
Technology in learning Arabic grammar can help students understand more easily and with fewer difficulties. Infographics are one of the alternatives of today's technology that aim to make learning information simple, exciting, and easy to understand. This study focuses on students' views on the need to develop web-based interactive infographic modules in learning Arabic grammar. This study uses the Design and Development Research approach. Researchers used questionnaire instruments to obtain analysis data related to learning materials, learning approach issues, the tendency to utilize innovation, and the need to use interactive infographics. A total of 205 students from Bachelor of Arabic Studies, UniSZA, who had taken Ibn Aqil's Syntax Text study, were made to be respondents that answered the questionnaire. Data were analyzed using the Statistical Package for Social Science (SPSS) software to obtain the mean and standard deviation. Interactive infographic content can attract students to understand complex lessons, and it should be developed.